2021
DOI: 10.3390/antiox10060877
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Ripening Stage and Extraction Conditions on the Phenolic Fingerprint of ‘Corbella’ Extra-Virgin Olive Oil

Abstract: The ancient ‘Corbella’ olive variety from the center-north of Catalonia is being recovered to obtain quality extra-virgin olive oil (EVOO) with unique organoleptic properties. The aim of this work was to determine the effect of agronomic and technical factors on the phenolic fingerprint of EVOO and to establish the optimum harvesting time and crushing and malaxation conditions for ‘Corbella’ olives. Therefore, three different ripening indices (0.3, 1.2, and 3.2) and three crushing temperatures (10, 18, and 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 59 publications
6
25
1
Order By: Relevance
“…A principal component analysis (PCA) was performed using SIMCA 13.0.3 to assess the impact of the different variables on our EVOO samples and see how they were distributed. The PCA indicated that the RI had a considerable impact on the phenolic profile of the olive oil, confirming previous reports [ 7 , 13 , 21 ]. The values of the RI were different depending on the olive tree from which the olives were collected ( Table A1 ).…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…A principal component analysis (PCA) was performed using SIMCA 13.0.3 to assess the impact of the different variables on our EVOO samples and see how they were distributed. The PCA indicated that the RI had a considerable impact on the phenolic profile of the olive oil, confirming previous reports [ 7 , 13 , 21 ]. The values of the RI were different depending on the olive tree from which the olives were collected ( Table A1 ).…”
Section: Methodssupporting
confidence: 89%
“…An increase in phenolic alcohols with temperature and time has been attributed to the hydrolysis of secoiridoids [ 7 , 25 , 36 ] and was more visible at temperature ranges above those tested here (>30 °C). Likewise, an increase in flavones could be attributed to the transformation of its glycosylated forms into the aglycones, increasing its solubility in the oil [ 13 ]. Contrary, phenolic acids showed a negative correlation with higher temperatures (20−60 °C) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smaller amounts of simpler phenolic compounds—such as caffeic, vanillic, and ferulic acids—have the role of protecting and enhancing the bioavailability of α-tocopherol [ 6 , 7 , 8 , 9 , 12 , 13 , 14 , 33 , 34 ]. See Table S2 for further information regarding antioxidants in the unsaponifiable fraction of EVOO from the main cultivars in the Mediterranean Area [ 17 , 19 , 20 , 21 , 22 , 23 , 25 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Chlorophyllic and carotenoid pigments.…”
Section: Resultsmentioning
confidence: 99%